FORENSIC NURSING PERFORMANCE UNDER THE PERSPECTIVE OF NURSING GRADUATION STUDENTS - Reis, Igor de Oliveira (2021)
Objective: to analyze the view of nursing students about the role of Forensic Nursing. Method: qualitative, descriptive and exploratory study, conducted with 10 nursing students from a private university in northern Brazil. A semi-structured interview was used, through the adaptation of the instrument called: Questionnaire of Knowledge on Forensic Nursing Practices. To categorize the statements, Content Analysis was used. Results: participants identified forensic nursing through some skills and competencies, as well as their field of work, assistance to forensic patients and institutional protocols. Conclusion: it was possible to understand how nursing students related forensic nursing as a field of action, bringing limitations of knowledge related to the concept of the specialty and the specificities of performance, with an emphasis on approaching and caring for people in situations of violence and technical procedures in the management of traces.